AN ANALYSIS OF ENGLISH LEXICAL COLLOCATION IN TRANSACTIONAL SPEAKING AMONG STUDENTS OF ENGLISH EDUCATION DEPARTMENT AT ALAUDDIN STATE ISLAMIC UNIVERSITY OF MAKASSAR - Nawir, Muhammad Syahruddin; Nur, Nur Aliyah; Nurul Hidayah, (English Language Teaching for EFL Learners Journal, 2022)
This study focused on the use of lexical collocations in transactional speaking skills of final year students majoring in English. This study aimed to determine the students ability in using lexical collocation and identifiy its type in their transactional speaking. The study conducted in Alauddin State Islamic University of Makassar. The subject of this study were the final year students of English Education Department. These students can be categorized as the intermediate learners of English because they took speaking lectures one to three. It was important for their collocational knowledge to be native-like. This study used a qualitative method. Researcher used interview as the data collection tool. Then, the researcher analysed the transcript of the interview. In analysing, researcher determined the collocation words and the types too, used Oxford online collocation dictionary to check whether the collocation were true or not. The findings showed that the students used English lexical collocations in their transactional speaking. Researcher found 179 English lexical collocations are used by the students. 81 of those collocations are correct. Researcher also found that they used four types from total 6 types (based on Benson&Ilson) of English lexical collocation which they tend to use the type 1 than the other types. The study therefore suggested that the teacher and students should more concerned about the collocational knowledge in this case lexical collocation.